Ex vivo normothermic preservation of a kidney graft from uncontrolled donation after circulatory death over 73 hours - Montagud-Marrahi, Enrique; Luque, Yosu; Ros, Ruben Rabadan; Ajami, Tarek; Cuadrado-Payan, Elena; Estrella, Hector; Arancibia, Andres; Sánchez-Etayo, Gerard; Bohils, Marc; Marrero, Ramsés; Fundora, Yilliam; Ramírez-Bajo, Maria José; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Transplant community is focused on prolonging the ex vivo preservation time of kidney grafts to allow for long distance kidney graft transportation, assess the viability of marginal grafts and to optimize a platform for the translation of innovative therapeutics to the clinical practice, especially those focused in cell and vector delivery to organ conditioning and reprogramming. We describe the first case of feasible preservation of a kidney from a donor after uncontrolled circulatory death over a 73-hour period using normothermic perfusion and analysing hemodynamic, biochemical, histological and transcriptomics parameters for inflammation and kidney injury. Mean pressure and flow values were of 71.24±9.62mmHg and 99.65±18.54mL/min, respectively. Temperature range was 36.7 to 37.2ºC. Renal Resistance Index was 0.75±0.15mmHg/mL/min. Mean pH was 7.29±0.15, lactate concentration peak increased until 213 mg/dL at 6 hours, reaching normal values after 34 hours of perfusion (8.92 mg/dL). Total urine output at the end of perfusion was 1.185mL. Histological analysis revealed no significant increase in Acute Tubular Necrosis severity as perfusion progressed. KIM-1, VEGF and TGFβ expression decreased after 6-18 hours of perfusion until 60 hours, when increased again together with β-catenin, Ki67 and TIMP1. We show that normothermic perfusion can maintain a kidney graft viable ex vivo for 3 days, thus allowing a rapid translation of pre-clinical therapeutics to clinical practice.